2010
DOI: 10.1162/evco.2010.18.1.18105
|View full text |Cite
|
Sign up to set email alerts
|

Strength Pareto Particle Swarm Optimization and Hybrid EA-PSO for Multi-Objective Optimization

Abstract: This paper proposes an efficient particle swarm optimization (PSO) technique that can handle multi-objective optimization problems. It is based on the strength Pareto approach originally used in evolutionary algorithms (EA). The proposed modified particle swarm algorithm is used to build three hybrid EA-PSO algorithms to solve different multi-objective optimization problems. This algorithm and its hybrid forms are tested using seven benchmarks from the literature and the results are compared to the strength Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Wang et al (2005) proposed a hybrid genetic algorithm that used both quantum-inspired operators as well as operators from the classical genetic algorithm); (2) hybridizing search and updating methods (e.g. Elhossini et al (2010) adapted the particle swarm algorithm for multi-objective optimization); or (3) hybridizing different methods in different search phases (e.g. Yang et al (2009) developed a hybrid algorithm that has three phases and different search methods are used in each).…”
Section: A Framework For Building Hybrid Pareto Front Generating Algomentioning
confidence: 99%
“…Wang et al (2005) proposed a hybrid genetic algorithm that used both quantum-inspired operators as well as operators from the classical genetic algorithm); (2) hybridizing search and updating methods (e.g. Elhossini et al (2010) adapted the particle swarm algorithm for multi-objective optimization); or (3) hybridizing different methods in different search phases (e.g. Yang et al (2009) developed a hybrid algorithm that has three phases and different search methods are used in each).…”
Section: A Framework For Building Hybrid Pareto Front Generating Algomentioning
confidence: 99%
“…Wang et al [32] developed a preference order to rank all the particles and thus to identified the global best particle. Elhossini et al [33] combined PSO with evolutionary algorithm and selected the global best particle from the external archive by a tournament selection. The personal best particle is selected as the one with lowest strength Pareto fitness.…”
Section: The Multi-objective Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…Tan et al [27] presented an adaptive variation operator that exploits the chromosomal structure of binary representation and synergizes the function of crossover and mutation. Elhossini et al [12] suggested a hybridization of particle swarm optimization (PSO) and genetic operators to handle MOPs, where genetic operators are modified to preserve the information used by PSO. Some recent similar works can be referred in [14,23,19,25].…”
Section: Variation Operators In Multi and Manyobjective Optimizationmentioning
confidence: 99%